Biomimetic DNA nanoballs for oligonucleotide delivery. (September 2015) - Kim, Mi-Gyeong; Park, Joo Yeon; Shim, Gayong; Choi, Han-Gon; Oh, Yu-Kyoung
Abstract: Here, we designed biomimetic DNA nanoballs for delivery of multiple antisense oligonucleotides (ASOs). DNA templates with ASOs-complementary sequences were amplified by rolling circle amplification (RCA). RCA products were loaded with two types of ASOs by hybridization, condensed using adenovirus-derived Mu peptide, and coated with hyaluronic acid (HA) for delivery into CD44-overexpressing tumor cells. HA-coated, Mu peptide-condensed, dual ASO-loaded DNA nanoballs (HMA nanoballs) showed considerable cellular entry of Cy5-incorporated RCA product DNA and fluorescent ASOs, whereas Mu peptide-condensed, dual ASO-loaded DNA nanoballs (MA nanoballs) revealed limited uptake. Dual ASOs, Dz13 and OGX-427, delivered by HMA nanoballs could reduce the levels of protein targets and exert anticancer effects. Enhanced tumor distribution was observed for fluorescent HMA nanoballs than the corresponding MA nanoballs. Upon intravenous co-administration with doxorubicin, HMA nanoballs exerted the greatest anti-tumor effects among the groups. These results suggest HMA nanoballs as a nanoplatform for sequence-specific delivery of multiple ASOs and other functional oligonucleotides.